Penelitian Tindakan Kelas Strategi Guru dalam Meningkatkan Minat Belajar Siswi SMP Al Mushlih Kelas VII pada Mata Pelajaran PAI - Ahmad Shofi; Selvy Julia Lestary; Syahla Nazihah; Nur Aini Farida (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study was conducted due to the low interest of seventh-grade students in learning Islamic Education (PAI) at SMP Al-Mushlih Telukjambe Timur, Karawang. The purpose of this research is to determine the improvement of students’ learning interest through the use of visual learning strategies. The method used was classroom action research conducted in two cycles. Contextual learning strategies were applied using visual media, and students’ interest was assessed through observation sheets. The results showed a significant increase in interest, from 50% before the action, to 70% in the first cycle, and 95% in the second cycle. In conclusion, the use of contextual visual learning strategies effectively improves students’ interest in learning Islamic Education. This approach offers benefits for both educators and students in creating more engaging and interactive learning environments.